Impact evaluation of cash and food transfers for the seasonal emergency safety net in Hajjah and Ibb Governorates, Yemen endline report - Schwab, Benjamin; Margolies, Amy; Hoddinott, John F. (International Food Policy Research Institute, 2013)
This report is the final impact evaluation of the World Food Programme’s Cash and Food transfer program in Yemen. The program operated in Hajjah and Ibb governorates within the larger Emergency Safety Net (ESN), which provides assistance to qualifying households in rural Yemen. The report details the relative effectiveness of each modality at alleviating food security among the targeted population.